Empowerment of Midwives in Increasing Knowledge as a Result of Malpractic Incidents Reviewed from the Legal Aspects in the Working Area of the Puskesmas Kerek Kabupaten Tuban - Kholifatul Ummah; Noenik Soekorini; Arkha Rosyaria Badrus; Hartoyo (Universitas STRADA Indonesia, 2024)
Kerek District is a densely populated area where the majority of the people work as traders and fishermen, urban education is still low, the people of Kerek District have middle and high school education, the average population is 67,163 people, consisting of 33,196 famale residents. and 33,967 people are famale. In the Kerek area there is 1 health center, 17 villages and 17 posts, where each village has 1 village midwife in each village sub-district who is tasked with monitoring the health of mothers and children so that the number of midwives follows number of midwives. Kerek Subdistrict Village includes 17 midwives and 1 Kerek Community Health Center coordinating midwife whose duties include providing private health services that serve maternal and child health in their work area, but are required to carry out supervision. The problem is that how many incidents of malpractice in Kerek sub-district carried out by midwives on women giving birth which causes harm to the patient, namely the baby dies, so the health sciences faculty collaborates with the Indonesian Midwives Assosiation Kerek sub-district branch and the Kerek Community Health Center to provide guidance and counseling to all village midwives in Kerek sub-district to improve service quality for patients with the aim to reducing maternal and infant morbidity and mortality.